Is Instagram Effective for Reproductive Health Promotion in Adolescents during the COVID-19 Pandemic? - Mediastuti, Fitriani; Revika, Era (Universitas Airlangga, 2023)
Background: The majority of teens have smartphones and are involved with digital media. Almost 45% of teens described being online